Airbnb as a tool for business promotion : creating a strategy for Massovka - Anisimova, Anastasiia; Gburíková, Alžbeta; Ngo, Tien Dung; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This bachelor thesis explores the potential of using Airbnb Experiences as a digital marketing tool for promoting creative workshops, focusing on the case of Massovka, an art studio based in Prague. The main aim is to develop a marketing strategy to help Massovka attract a new segment of customers through Airbnb and to evaluate how the platform’s features could support customer engagement and business growth. The research combines theoretical analysis of marketing models with qualitative research, including interviews with Massovka’s customers, Airbnb users and potential local clients. Analytical tools such as SWOT, IFE/EFE matrices are used to assess Massovka’s internal and external environment. A perceptual map is used to evaluate Airbnb as a tool for promoting services in comparison to other key players in the travel and experience industry. Based on the findings, a marketing strategy is created using the STDC model, focusing on promoting sweets workshops as an entry point to Airbnb Experiences. Expert evaluation confirms the strategy’s practical applicability, highlighting its alignment with Massovka’s brand values and the behavioural patterns of Airbnb’s audience. The results show that Airbnb integration offers Massovka a realistic and sustainable path for customer growth, provided that early engagement challenges are actively managed. This thesis contributes to a better understanding how creative businesses can adapt digital platforms traditionally associated with tourism to strengthen their market position.
Vedoucí práce: Alžbeta Gburíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses